2020
DOI: 10.1007/s00710-020-00723-x
|View full text |Cite
|
Sign up to set email alerts
|

The parisite–(Ce) enigma: challenges in the identification of fluorcarbonate minerals

Abstract: A multi-methodological study was conducted in order to provide further insight into the structural and compositional complexity of rare earth element (REE) fluorcarbonates, with particular attention to their correct assignment to a mineral species. Polycrystals from La Pita Mine, Municipality de Maripí, Boyacá Department, Colombia, show syntaxic intergrowth of parisite–(Ce) with röntgenite–(Ce) and a phase which is assigned to B3S4 (i.e., bastnäsite-3–synchisite-4; still unnamed) fluorcarbonate. Transmission e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 63 publications
(111 reference statements)
0
9
0
Order By: Relevance
“…This has been done previously in the literature, as for instance, to observe Nd 3+ in parisite–(Ce). [ 65 ] In that case, under 532 excitation (Figure 5 in that paper), additional unassigned emission bands were observed at approximately 16,800, 15,400, and 14,200 cm −1 (595, 649, and 704 nm), which according to the data in Table 1 correspond to the emissions of Sm 3+ . Figure S8 shows the emission spectra of a crystal of apatite excited with the argon laser lines at 488 and 514.5 nm which reveal a strong Sm 3 + 4 G 5/2 – 6 H 9/2 emission at approximately 650 nm under 488 nm excitation and the Nd 3 + 4 F 5/2 – 4 I 9/2 emission at approximately 800 nm under 514.5 nm excitation.…”
Section: Discussionmentioning
confidence: 76%
“…This has been done previously in the literature, as for instance, to observe Nd 3+ in parisite–(Ce). [ 65 ] In that case, under 532 excitation (Figure 5 in that paper), additional unassigned emission bands were observed at approximately 16,800, 15,400, and 14,200 cm −1 (595, 649, and 704 nm), which according to the data in Table 1 correspond to the emissions of Sm 3+ . Figure S8 shows the emission spectra of a crystal of apatite excited with the argon laser lines at 488 and 514.5 nm which reveal a strong Sm 3 + 4 G 5/2 – 6 H 9/2 emission at approximately 650 nm under 488 nm excitation and the Nd 3 + 4 F 5/2 – 4 I 9/2 emission at approximately 800 nm under 514.5 nm excitation.…”
Section: Discussionmentioning
confidence: 76%
“…Some studies have reported the measurement of F in cerianite by EPMA 12 ; however, potential interferences should be considered. The EPMA analyses of the synthetic F‐free CePO 4 showed an apparent 1.1 wt.% F. The apparent concentrations are due to the interference from the 2nd order of the Mz line of Ce on the fluorine Kα line 48 . After the correction for interference, the estimated 0.22 wt.% F concentrations in supergene cerianite were indistinguishable from the detection limit of 0.16–0.18 wt.% of the method (Table 2), and we concluded that our supergene cerianite has negligible F content.…”
Section: Discussionmentioning
confidence: 97%
“…The range of δ 34 S values is close to that of magmatic fluids, namely 0‰ -5‰, similar with tin deposits in Brazilian Rondonia. However, in the context of the study area, the value of δ 34 S is slightly more enriched, possibly influenced by an igneous sulphide reservoir that has a value range of -2 ‰ to + 35 ‰ [40]. Kelabat granite is the closest surrounding rock, it may be a stable isotope source of S for the sulphide mineralizing-hydrothermal fluid.…”
Section: Characteristics and Composition Of Hydrothermal Fluidmentioning
confidence: 91%